2018
DOI: 10.1044/2018_ajslp-17-0138
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Responsiveness to Gestures in Children With Down Syndrome

Abstract: Young children with DS gesture more than chronological age-matched children with TD, therefore providing numerous opportunities for caregivers to recode child gestures and support language development. Early intervention should focus on increasing parent responsiveness to child gestures earlier in life in order to provide additional word-learning opportunities for children with DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
(103 reference statements)
1
16
0
Order By: Relevance
“…For populations with gesture strengths, such as DS, 17,81,89 more instances of word-referent transparency may be driven by the child as illustrated by two of our three case examples. For children with weakness in gesture, such as those with FXS, [18][19][20]90 it may be even more difficult for mothers of children with FXS to provide follow-in comments because their children are not using gestures frequently.…”
Section: Implications For Maximizing Input Quality For Children With Neurogenetic Disordersmentioning
confidence: 76%
See 3 more Smart Citations
“…For populations with gesture strengths, such as DS, 17,81,89 more instances of word-referent transparency may be driven by the child as illustrated by two of our three case examples. For children with weakness in gesture, such as those with FXS, [18][19][20]90 it may be even more difficult for mothers of children with FXS to provide follow-in comments because their children are not using gestures frequently.…”
Section: Implications For Maximizing Input Quality For Children With Neurogenetic Disordersmentioning
confidence: 76%
“…Research suggests that mothers recode the gestures used by children with DS, providing linguistic input related to their children's nonverbal communication. 81 For example, the child points to a picture of a dog and their mother responds, "That's a dog." Interestingly, mothers of children with DS and with typical development recode a similar amount of gestures.…”
Section: Case Examples Of Toddlers With Down Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that mothers take into account child gesture and sign language use when providing linguistic input. Studies have demonstrated that mothers of children with DS are able to acknowledge and respond to child signs and gestures (Dimitrova et al, 2016;Lorang, Sterling, & Schroeder, 2018). It may be the case that mothers adjust their language based on their child's gestures or total communication attempts (i.e., the combination of gestures, vocalizations, and verbalizations rather than just verbalizations) when communicating with young children with DS, particularly given that gestures are often the primary means of communication for an extended period of time in children with DS.…”
Section: Research Question 2: Examining Relationships Between Maternamentioning
confidence: 99%